MENINGKATKAN KEMAMPUAN BERBICARA SISWA DI SMA NEGERI 1 BEO DENGAN MENGGUNAKAN TEKNIK IMITASI - Tempoh, Juanri H. B.; Warouw, Maya P.; Jansen, Frieda Th. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACT This research entitled â€œimproving students speaking skill through imitation techniqueâ€ is implemented in SMA Negeri 1 Beo. It is attempted to apply the imitation technique in English (language). This research is expected for student acquirement the language by copying the utterance through imitation model. Theoretically imitation technique is used to copying the utterance without observing the grammatical rule. The learner acquires the language as a child learns a language. The imitation technique makes the learner knows not only what they say but also how to say it. However, the technique is more enjoyable to it push the learner to copy the utterance from the model. In this study the writer applied four types of imitation: observing, remembering, reproducing and reinforcing or motivational. The research uses classroom action research. The result of this research shows that imitation technique can improve studentsâ€™ speaking skill through classroom activity research. All students have more than 50% improvement. Keywords: imitation technique, speaking skill and classroom action research.